2015
DOI: 10.1016/j.powtec.2014.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Stages in spheronisation: Evolution of pellet size and shape during spheronisation of microcrystalline cellulose-based paste extrudates

Abstract: The stages of extrudate breakup and rounding to form spheroidal pellets were investigated for MCC/water pastes and some MCC/water/calcium carbonate pastes using the interrupted technique reported by Lau et al. (2014). A new quantitative parameter, named 'dumb-bellity', was developed to monitor the formation and disappearance of 'dumb-bell' shaped pellets in the early stages of the rounding process. Tests using mixtures of coloured extrudates confirmed that attachment of small fragments ('fines') to the waist o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 19 publications
3
23
0
1
Order By: Relevance
“…This was confirmed in the current study by high speed video monitoring of the spheronisation step. Lau et al did not observe twisting, associated with the Baert et al [6] mechanism, whilst subsequent studies on similar MCC/water pastes by Bryan et al [1] indicated that the mechanism of fines specifically collecting at the waist (as described by Liew et al [7]) was not responsible for the transition from dumb-bell to more spherical shape.…”
Section: Introductionmentioning
confidence: 94%
“…This was confirmed in the current study by high speed video monitoring of the spheronisation step. Lau et al did not observe twisting, associated with the Baert et al [6] mechanism, whilst subsequent studies on similar MCC/water pastes by Bryan et al [1] indicated that the mechanism of fines specifically collecting at the waist (as described by Liew et al [7]) was not responsible for the transition from dumb-bell to more spherical shape.…”
Section: Introductionmentioning
confidence: 94%
“…The average pellet surface tensile strength data in Figure 5 show a statistically significant effect of D on pellet tensile strength (F = 24.525, P = 0). The strengths of the pellets from D = 1.5, 2.0 and 2.5 mm extrudates are not statistically different (P(Welch test) = 0.054, P(Brown- 19 Forsythe test) = 0.129), while the strength of the pellets generated from D = 1.0 mm extrudates is significantly higher (see the Post Hoc Least Squares Difference (LSD) results in Table 6).…”
Section: Pellet Surface Tensile Strengthmentioning
confidence: 99%
“…This study extends earlier work [24] on the influence of extrudate diameter, D, and protuberance dimensions. Testing employed a 45 wt% MCC/water paste which has been employed previously as a model formulation to investigate E-S mechanisms [6,19,[24][25][26].…”
Section: Schmidt and Kleinebuddementioning
confidence: 99%
See 1 more Smart Citation
“…[4]. Since the pellets have a cylindrical shape at the beginning of the spheronization process and undergo different stages of deformation (cylindrical -dumbbell -spherical) during the rounding process [5][6][7], this contribution focuses on the influence of the particle shape on the particle dynamics. The simulation results provide information about the influence of the particle shape on the particle flow regime and the mixing of the particle torus, as well as the influence on the collision rates and forces.…”
Section: Fig 1 Spheronizer Geometry Used In the Simulationsmentioning
confidence: 99%